Libre comercio y regionalismo subsupranacional - Daher, Antonio (Revista EURE - Revista de Estudios Urbano Regionales, 1997)
This article presents three central theses: the first states that, both the Í€œinternationalizationÍ€ of exterior commerce -through intra-area commerce and geo-economic blocks- and the high territorial concentration of the economy and its local market character of comparative advantages show that neither globalization or technological support have dislocated or disterritorialized the economy. The second thesis states that the territorial adjustments associated with economic liberalization and aperture, anticipate the regional and urban impacts of free trade agreements. These impacts will be more convergent with the agreements the more open the regionalism that inspires them. Nevertheless, the regional effects of any agreement can be extremely disparate. These could favor more or less certain regions while damaging others. The third thesis shows that, as a consequence, regions should have a growing participation in the political and international economy. As much for decentralization as for the mega-markets, local public policy must globalize itself to the point of making itself Í€œcommunitarianÍ€, strained between the sub-supranational polarity. Í